Using Genetic Diversity of Dendrocalamus strictus Nees. for Increasing Productivity of Bamboo Plantations in Vindhyan Region of Uttar Pradesh - Kumari, Niwedlta; Singh, Pradeep; Srivastava, Ram Jee; Mishra, C.M.; Dubey, Prabhakar; Burfal, B. S. (Indian Forester, 2001)
The study of genetic diversity of Dendrocalamus strict us Nees for increasing the productivity of Bamboo plantation in Vindhyan Region of Uttar Pradesh was confined to diameter and volume of culm, which are the major traits for better quality of Bamboo. The rhizomes of one year old culms were collected from the different CPCs as selected in Renukoot, Mirzapur and Obra Forest Divisions. The collected rhizomes were raised at Research Nursery, Kotwa, Mirzapur for ex-situ conservation. Significant variations were observed in diameter of the culm and volume along with culm height among all the 12 CPCs. It provides a clear cut indication for good selection of CPCs for cultivation at Mirzapur and adjoining places for improvement and multiplication of good quality bamboo vis-a-vis enhancing the yield.